HOW TO WRITE A NARRATION - Katya Tahchieva (Педагогически форум)
The present work is part of a research paper for which I extend my heartfelt thanks to Assoc. Prof. Dr. Valko Kanev. It examines some specifics of the artistic creation process that lead to the creation of one of the types of written student texts - the narration. Its variations - "narration by imagination" and "narration by set supports" are regulated in the new fifth grade curriculum. The requirements for writing a narration and the exemplary thematic curriculum of optional literature classes in the 7-t grade have proven to be applicable in the literature education process.